(Des)caminhos da pós-graduação brasileira: o produtivismo acadêmico e seus efeitos nos professores pesquisadores - Pimenta, Alessandra Giuliani (2014)
This thesis is linked to a research called `Teaching and learning Process in the Post Graduation Course in Education' at the Federal University of Paraiba and brings up the discussion about academic productiveness through the Brazilian Post Graduation programs passing by the knowledge-power relation established nowadays, and Researchers-professors's subjectiveness are affected in this process. The aim of this paper is to extend the productive policies, its demands and effects on the post graduation teaching activities. Here, the core of Brazilian Education and the neoliberal model are questioning besides the current university and its demands on the post graduation course and also the academic productiveness and its developments in the researcher`s daily practice. The perspective of this work is the Michel Foucault`s Analytical and the three domains of his work (knowledge, power and achievement), together with other interpreter`s contributions and some authors having the same line of thoughts. The methodology was done after analyzing some professors`s speeches and documents provided by CAPES in which we find topics related to the post graduation course. In this regard, individual interviews were carried out and the interviewees have written a letter which has been published and the publications are relevant for this theme. The analysis were built from links between theoretical-perspectives and from Foucault`s concepts. The results demonstrate the devastating effects in the professor`s life caused by these policies. Therefore, the intention was to discuss the relations, here established, look for escape and find a different look and thought about the education and its post graduation model which massify the picture of professors and then understand its effects and reframe its process